Synthesis and antimicrobial activity of Schiff and Mannich bases of isatin and its derivatives with pyrimidine - Pandeya S.N.; Sriram D.; Nath G.; De Clercq E. (My University, 2025)
Isatin and its derivatives have been reacted with 4-(4'-chlorophenyl)-6-(4''-methyl phenyl)-2-aminopyrimidine to form Schiff bases and the N-Mannich bases of these compounds were synthesized by reacting them with formaldehyde and several secondary amines. Investigation of antimicrobial activity of the compounds was made by the agar dilution method against 28 pathogenic bacteria, eight pathogenic fungi and anti-HIV activity against replication of HIV-1 (III B) in MT-4 cells. The compounds are significantly active against bacteria and fungi. Copyright (C) 1999 Elsevier Science S.A.